1996
DOI: 10.1016/s0042-6989(96)00131-9
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic modulation of dopamine release and horizontal cell coupling in mudpuppy retina

Abstract: The effects of cholinergic agonists and antagonists on electrical coupling between horizontal cells were studied in dark-adapted mudpuppy retinas. Carbachol and the nicotinic agonist 1,1-dimethyl-4-phenylpiperazinium (DMPP) uncoupled horizontal cells, but the muscarinic agonist oxotremorine did not. The uncoupling effects of carbachol and DMPP were blocked by the nicotinic antagonist D-tubocurarine and by the dopamine antagonist fluphenazine, indicating that carbachol uncoupled horizontal cells by stimulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…It is possible that photoreceptors lack some binding element that paraformaldehyde can cross-link with DAF to retain activated DAF within the photoreceptors. The increased NO-IF in horizontal cells may be related to the uncoupling effects of cholinergic agonists that have been reported in horizontal cells in mudpuppy retina (Myhr & McReynolds, 1996). Thus there is no indication that fixation produces any artifactual production of NOIF or DAF activation and that in some cell types there can be a decrease in NO-IF in response to fixation.…”
Section: Aldehyde Fixation Of Dafmentioning
confidence: 72%
“…It is possible that photoreceptors lack some binding element that paraformaldehyde can cross-link with DAF to retain activated DAF within the photoreceptors. The increased NO-IF in horizontal cells may be related to the uncoupling effects of cholinergic agonists that have been reported in horizontal cells in mudpuppy retina (Myhr & McReynolds, 1996). Thus there is no indication that fixation produces any artifactual production of NOIF or DAF activation and that in some cell types there can be a decrease in NO-IF in response to fixation.…”
Section: Aldehyde Fixation Of Dafmentioning
confidence: 72%
“…Cholinergic modulation of dopamine release has been found in the mudpuppy (Myhr and McReynolds, 1996), fish (Negishi and Drujan, 1979), tiger salamander (Hare and Owen, 1995), chick (Schwahn et al, 2000), and rabbit retinas (Neal et al, 2001). Despite these similarities, there are some species variations in the localization and function of cholinergic signaling components.…”
Section: Previous Localization Of Ach and Machrs In The Retina; Functmentioning
confidence: 99%
“…In the tiger salamander, Marshall and Werblin (1978) showed that ACh application uncoupled horizontal cells, consistent with the idea of cholinergic signaling in the outer retina. Studies in the salamander and mudpuppy retina later stated that this was due to an increased release of dopamine mediated by nAChRs (Hare and Owen, 1995;Myhr and McReynolds, 1996). However Myhr and McReynolds (1996) used fluphenazine as a dopaminergic antagonist, and since fluphenazine also antagonizes calmodulin, any cholinergic interaction with the NO signaling pathway would also have been blocked because activated calmodulin is required for NO synthesis by NOS.…”
Section: Previous Localization Of Ach and Machrs In The Retina; Functmentioning
confidence: 99%
“…Nitric oxide increases the levels of cyclic guanosine monophosphate in overlapping populations of retinal cells 27 . Nicotine also serves as a modulatory transmitter, increasing dopamine release and modulating horizontal cell coupling 28 …”
Section: Discussionmentioning
confidence: 99%
“…27 Nicotine also serves as a modulatory transmitter, increasing dopamine release and modulating horizontal cell coupling. 28 Nicotine addiction leads to withdrawal symptoms in many persons who quit smoking. Nicotine receptors in the central nervous system are located mainly in presynaptic membrane and in that way they regulate the release of several neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%